Screening of antimicrobial producing strains isolated from the soil of grassland rhizosphere in Pocut Meurah Intan Forest Park, Seulawah, Aceh Besar - LENNI FITRI; BETTY MAULIYA BUSTAM (Society for Indonesian Biodiversity, 2010)
Fitri L, Bustam BM (2010) Screening of antimicrobial producing strains isolated from the soil of grassland rhizosphere in PocutMeurah Intan Forest Park, Seulawah, Aceh Besar. Biodiversitas 11: 129-132. This research was a part of some works that wasconducted to find antibiotics from soil microbes. The aim of this research was to screen isolates of antibiotics-producing microbes. Soil samples were collected from grassland rhizosphere in Pocut Meurah Intan Natural Reserved Forest Seulawah, Aceh Besar. This research was conducted at the microbiology laboratory Department of Biology , Faculty of Mathematics and Natural Sciences, Syiah Kuala University. This research covers six steps i.e. collecting soil samples, isolation of microbes, making colony library, purifying colony library, antagonism test and disk method test. Eleven isolates of microbes were selected, and purified for colony, library. However, only six isolates were assumed to have an ability to produce antibiotics, as confirmed by antagonism test. Those isolates have greater ability to inhibit the growth of Staphylococcus aureus than that of Escherichia coli. 13.25 mm was The average of clear zones formed for Staphylococcus aureus and Escherichia coli were 13.25 and 11.33 mm, respectively.Key words: grassland rhizosphere, antibiotic, microbes.